(untitled) (Research, Society and Development, 2022)
The objective of the present study was to survey the biodiversity of scarab beetles in the Córrego do Café region in Ituiutaba (MG), as well as their ecosystem functions. The study was carried out in the portions of riparian forests of the Café stream located at the Experimental Farm of the University of the State of Minas Gerais (UEMG), Ituiutaba Unit (MG). The collections of scarab beetle species (Coleoptera: Scarabaeidae) took place between March and June 2018. To identify the scarab beetle, traps were installed in the areas of native vegetation, agriculture and pasture, of the ptifall type, buried at the level of the soil, spaced 50 m apart and baited with swine feces (25 g). After 24 hours, the captured beetles were sorted and accommodated in blankets, produced with newspaper and cotton, and stored for later identification. To evaluate ecosystem functions, two arena-type traps were installed, spaced 100 m apart and filled with 300 g of baits composed of pig and cattle manure. The soil stirred up by the beetles was dried at 60°C for three days and weighed. The results were significant for all variables in relation to land use, that is, according to the evaluated phytophysiognomy, differences were presented. Because the environment is a strong influencer of biodiversity. Thus, most of the individuals were found in forest areas, followed by pasture areas and finally, areas of agriculture composed of sugarcane, which were the ones with the lowest abundance of scarab beetles.